Thermoanalytical, spectroscopic and DFT studies of heavy trivalent lanthanides and yttrium(III) with Oxamate as Ligand - Caires, Flávio Junior [UNESP]; Nunes, Wilhan Donizete Gonçalves [UNESP]; Gaglieri, Caroline [UNESP]; Do Nascimento, André Luiz Carneiro Soares [UNESP]; Teixeira, José Augusto [UNESP]; Zangaro, Geórgia Alvim Coelho [UNESP]; Treu-Filho, Oswaldo [UNESP]; Ionashiro, Massao [UNESP] (FapUNIFESP (SciELO), 2017)
Solid-state LnL3·nH2O complexes, where Ln stands for trivalent lanthanides (Tb to Lu) or yttrium(III) and L is oxamate (NH2COCO2-), have been synthesized. The characterization of the complexes was performed by using elemental analysis (EA), complexometric titration with EDTA, thermoanalytical techniques such as simultaneous thermogravimetry and differential scanning calorimetry (TG-DSC), evolved gas analysis (TG-FTIR), infrared spectroscopy (IR) and powder X-ray diffraction (XRPD). The results provided information about thermal behavior, crystallinity, stoichiometry, coordination sites, as well as the products released during thermal degradation of the complexes studied. Theoretical calculation of yttrium oxamate, as representative of all complexes was performed using density functional theory (DFT) for studying the molecular structure and vibrational spectrum of the investigated molecule in the ground state. The optimized geometrical parameters and theoretical vibrational spectrum obtained by DFT calculations are in good agreement with the experimental results.
Keywords: DFT calculations; Lanthanides; Oxamic acid; Thermal analysis